Analysis of the Impact of Cash Budget on Operating Profit at PT. ACE Hardware Indonesia Tbk for the Years 2021-2023 - Novanda, Shopi Sherima; Rostina, Tina (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2024)
This study aims to analyze the operating profit, cash budget, and financial ratios of PT. ACE Hardware Indonesia Tbk from 2021 to 2023. This research adopts a descriptive approach with a qualitative method. The data used in this study is secondary data. The data collection techniques include documentation and literature review. The documents utilized are secondary data obtained from financial reports listed on the Indonesia Stock Exchange. The findings reveal that PT. ACE Hardware Indonesia Tbk's operating profit fluctuated between 2021 and 2023, indicating changes in the company’s financial performance. This study highlights the significance of effective cash budget management in enhancing operating profit, controlling costs, and maintaining the company’s liquidity.